Low-dose curcumin-loaded Eudragit L-100-nanocapsules in the diet of dairy sheep increases antioxidant levels and reduces lipid peroxidation in milk - Jaguezeski A.M.* (2019)
© 2019 Wiley Periodicals, Inc.The main objective of this study was to evaluate whether the addition of curcumin-loaded nanocapsules (prepared and characterized) in the diets of dairy sheep improved milk quality. The nanocapsules were prepared using two polymers: poly-ε-caprolactone (PCL) and Eudragit L-100. The nanocapsules contained 0.25 mg/ml (Nano-Eudragit L-100) and 2 mg/ml (Nano-PCL) of curcumin. Dairy sheep were divided into four groups: A (control), B (30 mg free curcumin/kg concentrate), C (3 mg Nano-PCL/kg concentrate), and D (3 mg Nano-Eudragit/kg concentrate). We observed that the number of total leukocytes and serum globulin levels were lower in Group D than in the control (Group A) (p < 0.05). Antioxidant capacity against peroxyl radicals (ACAP) and catalase enzymes was elevated in Group D, with consequently reduced lipid peroxidation (LPO; p < 0.05). In milk, there were no differences in production and composition between groups during the experimental period (p > 0.05); however, ACAP increased and LPO decreased in milk. Practical applications: Curcumin is a functional molecule with potent antioxidant, anti-inflammatory, and antimicrobial actions, used frequently and with medical indications in human food. Free curcumin in sheep diets improves milk quality and increases its shelf life. This study showed that curcumin nanocapsules produced from the Eudragit L-100 polymer potentiated the anti-inflammatory and antioxidant actions of dairy sheep when used in the diet daily, at doses 10 times lower than that of free curcumin. These positive effects were reflected in higher total antioxidant capacity and lower lipid peroxidation in milk in sheep-fed curcumin-loaded Eudragit L-100 nanocapsules, generating desirable milk properties. In practice, the use of nanotechnology enhances the beneficial effects of curcumin in milk, possibly creating a nutraceutical food desirable to consumers.